Conocimientos y actitudes hacia la vacuna contra COVID-19 en personas de 18 a 85 años asentamiento humano Bella Luz Iquitos 2023 - Reguera Arrunategui, Keiko Akira (2024)
The objective of the study was to determine the relationship between knowledge and attitude towards the COVID-19 vaccine in people between 18 and 85 years of age of both sexes from the Bella Luz Human Settlement, Iquitos 2023. The approach was quantitative, the design was non-experimental of a correlational type and the sample was 87 people. The technique was the interview and two instruments were used, the knowledge questionnaire about the COVID-19 vaccine (Validity 97.66% and reliability 95.80%) and the attitude scale towards the COVID-19 vaccine (Validity 96.88%). %). % and reliability 94.79%). Results: In terms of knowledge, 60.9% had poor knowledge, 28.7% had regular knowledge and 10.3% had good knowledge. In attitude towards the COVID-19 vaccine, 63.2% had a negative attitude and 36.8% had a positive attitude. By applying the Chi Square statistical contrast, statistical significance was determined (X 2 = 63.547; df = 2; p = 0.000; α = 0.05). Conclusion: It was determined that people enter 18 and 85 years of age of both sexes had little knowledge and negative attitude towards the COVID-19 vaccine, there being sufficient evidence of the relationship between knowledge and attitude towards the COVID-19 vaccine.